Corn Yield Response to Nitrogen in North-Central Kansas - A. A. Correndo; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2020)
The aim of this study was to evaluate the response of corn (Zea maysL.) grain yield to nitrogen (N) fertilizer. During the 2019 cropping season, an N rate experiment in corn was established in Scandia, KS, evaluating five N fertilizer rates as UAN (28-0-0) under both dryland and irrigated conditions. Average yields ranged from 138 to 236 bu/a under rainfed and from 153 to 249 bu/a for irrigated conditions. Under both dryland and irrigated conditions, maximum yields were achieved with an N rate of about 161 lb/a. Total N supply was calculated as N at planting plus fertilizer was approximately 300 lb N/a.
Keywords: yield response; maize; productivity; corn